HIGH YIELDING, ADAPTIVE VARIETIES OF QUINCE (British Journal of Global Ecology and Sustainable Development, 2023)
This article presents the results of studies conducted on quince and breeding for high-yielding, disease-resistant varieties. The best result was noted in the “Olmabekhi-applequince” variety with a yield of 200 c/ha and an additional yield of 23.8 c/ha compared to the standard variety.